2015
DOI: 10.1134/s1061920815030097
|View full text |Cite
|
Sign up to set email alerts
|

K-theory of noncommutative Bieberbach manifolds

Abstract: We compute K-theory of noncommutative Bieberbach manifolds, which quotients of a three-dimensional noncommutative torus by a free action of a cyclic group Z N , N = 2, 3, 4, 6.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…The classical limit of presented noncommutative geometries might have a place in the studies of models of flat compact space geometries in the context of cosmology [8]. The construction of different inequivalent spectral triples might suggest that there might be some differences between particle models built using them, in particular, twisting the obtained geometries with the projective modules, which represent nontrivial torsion in the K-theory of these objects [9].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The classical limit of presented noncommutative geometries might have a place in the studies of models of flat compact space geometries in the context of cosmology [8]. The construction of different inequivalent spectral triples might suggest that there might be some differences between particle models built using them, in particular, twisting the obtained geometries with the projective modules, which represent nontrivial torsion in the K-theory of these objects [9].…”
Section: Discussionmentioning
confidence: 99%
“…Proof. In [9] we showed that the crossed product algebra A(T 3 θ ) ⋊ Z N is isomorphic to the matrix algebra of the noncommutative Bieberbach manifold algebra:…”
Section: Spectral Triples Over Bieberbachsmentioning
confidence: 99%
See 3 more Smart Citations